Perceptions of national wealth and skill influence pay expectations: replicating global hierarchy on a microscale - Maitner, Angela T.; DeCoster, Jamie (Frontiers in Psychology, 2015)
In highly multicultural societies, the economic status hierarchy may come to mimic the hierarchy of global wealth, reinforcing social inequality by tying pay scales to national wealth. We investigated how nationality influences expectations of payment in the UAE. Participants reported how much they expected people to be paid and how much skill they were perceived to have by nationality. They also reported their perceptions of the national wealth of different countries. Participants generally expected Westerners to be paid more than Arabs, who would be paid more than Sub-Saharan Africans and Asians. Expectations about payment in private sector employment were driven by both actual and stereotyped differences in national wealth and skill, with non-Gulf Cooperation Council Arabs most likely to see national wealth as a factor explaining the economic hierarchy. These results suggest that people expect payment to be tied to national wealth, reflecting the global hierarchy on a microscale.